BAROCATOLOGY IN THE QUR'AN "MODERN ESSENCE AND IMPLICATIONS" - Ibnu Arbi Tarigan; Annisa Mawaddah (SOSIOEDUKASI, 2026)
This paper explores the Qur’anic concept of barakatology, an in-depth reflection on the essence of barakah (divine blessing) as the spiritual foundation of human life. The study employs a thematic (tafsir maudhu‘i) approach combined with a linguistic examination of the term barakah across its various contexts in the Qur’an. It aims to uncover the meanings, dimensions, and implications of barakah in shaping a life that harmonizes spirituality with social reality. The findings indicate that barakah extends beyond material prosperity; it encompasses inner serenity, ecological balance, and social harmony. From a Qur’anic perspective, barakah represents the manifestation of divine mercy that arises when human beings align their lives with the principles of tawhid (monotheism), justice, and sincerity. Conceptually, barakatology comprises three core dimensions: (1) the essence of barakah as a divine gift originating from God; (2) the manifestation of barakah through equilibrium between spiritual and social aspects; and (3) its practical dimension, guiding humanity toward a just and sustainable way of life. In the modern era marked by materialism and moral decline the values of barakah offer a spiritual paradigm that redefines progress not by luxury or accumulation, but by the extent to which life generates benefit, harmony, and peace for all creation.